2019
DOI: 10.1101/793752
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential protein metabolism and regeneration in hypertrophic diaphragm and atrophic gastrocnemius muscles in hibernating Daurian ground squirrels

Abstract: 41Whether differences in regulation of protein metabolism and regeneration are involved in the 42 different phenotypic adaptation mechanisms of muscle hypertrophy and atrophy in hibernators? 43Two fast-type muscles (diaphragm and gastrocnemius) in summer active and hibernating Daurian 44 ground squirrels were selected to detect changes in cross-sectional area (CSA), fiber type 45 distribution, and protein expression indicative of protein synthesis metabolism (protein expression 46 of P-Akt, P-mTORC1, P-S6K1, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…In this issue of Experimental Physiology , Yan et al. (2021) shed light on the distinctive features of the molecular mechanisms involved in the development of the hypertrophic response in the diaphragm and the atrophic response in the gastrocnemius muscle in hibernating Daurian ground squirrels. In particular, the authors showed that a decrease in protein synthesis, an increase in protein degradation and a decrease in muscle regeneration potential contributed to the atrophy of the gastrocnemius muscles during torpor, while an increase in protein synthesis, a decrease in protein degradation and an increase in muscle regeneration potential contributed to diaphragm muscle hypertrophy.…”
mentioning
confidence: 99%
“…In this issue of Experimental Physiology , Yan et al. (2021) shed light on the distinctive features of the molecular mechanisms involved in the development of the hypertrophic response in the diaphragm and the atrophic response in the gastrocnemius muscle in hibernating Daurian ground squirrels. In particular, the authors showed that a decrease in protein synthesis, an increase in protein degradation and a decrease in muscle regeneration potential contributed to the atrophy of the gastrocnemius muscles during torpor, while an increase in protein synthesis, a decrease in protein degradation and an increase in muscle regeneration potential contributed to diaphragm muscle hypertrophy.…”
mentioning
confidence: 99%